2021
DOI: 10.3384/ecp1809
|View full text |Cite
|
Sign up to set email alerts
|

PoetryLab as Infrastructure for the Analysis of Spanish Poetry

Abstract: The development of the network of ontologies of the ERC POSTDATA Project brought to light some deficiencies in terms of completeness in the currently available European poetry corpora. To tackle the issue in the realm of the Spanish poetic tradition, our approach consisted in designing a set of tools that any scholar could use to automatically enrich the analysis of Spanish poetry. The effort crystallized in the PoetryLab, an extensible open source toolkit for syllabification, scansion, enjambment detection, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Storage of one of the most consumed edible mushrooms, Agaricus bisporus, was analysed considering that commercial value and acceptability demand an attractive appearance and absence of deteriorating microorganisms. Films based on chitosan and dextran produced by Leuconostoc mesenteroides were analysed according to dextran concentration (from 0 to 4%, w/ v), physical-chemical properties, mechanical characteristics, permeability, and functionality of the biopackaging (D ıaz-Montes et al, 2021). The authors observed Roy & Rhim (2020) produced EPS-based films with pullulan e carrageenan, adding nanoparticles of copper sulphide and D-limonene.…”
Section: Antimicrobial Filmsmentioning
confidence: 99%
“…Storage of one of the most consumed edible mushrooms, Agaricus bisporus, was analysed considering that commercial value and acceptability demand an attractive appearance and absence of deteriorating microorganisms. Films based on chitosan and dextran produced by Leuconostoc mesenteroides were analysed according to dextran concentration (from 0 to 4%, w/ v), physical-chemical properties, mechanical characteristics, permeability, and functionality of the biopackaging (D ıaz-Montes et al, 2021). The authors observed Roy & Rhim (2020) produced EPS-based films with pullulan e carrageenan, adding nanoparticles of copper sulphide and D-limonene.…”
Section: Antimicrobial Filmsmentioning
confidence: 99%
“…Their approach achieved considerable accuracy, although the corpus focused on was still limited to classical sonnets. Other researchers have also proposed methods for using artificial intelligence to study Spanish poetry, but this research was carried out from the perspective of linguistics, such as consideration of prosody or the rhythm of the poetry [22,23]. All the aforementioned studies have provided technical and ideological inspiration that has contributed to the development of the current research.…”
Section: Spanish Text Classificationmentioning
confidence: 99%